Impact of Tax Rate Changes on Earnings Quality: Evidence from the UK - Shah, Chiraag (2016)
The paper aims to ascertain whether there is an impact on the quality of earnings reported by corporates from changes in tax rates and to conclude whether any correlation exists between the tax rate changes and the current and discretionary accruals of the UK companies. The study hypothesizes whether a fall in the corporate tax rate would or would not reduce the company’s accruals in the year before a tax rate reduction. Findings of the research (as statistically illustrated by the multiple regression analysis) reveal that 17.2% of the variation in current accruals is attributable to changes on net income, debt, changes in top line, market capitalization, and the decrease in tax. It thus follows that tax decrease, market capitalization of the firm, and changes in total revenue have a significant effect on the discretionary accruals. The null hypothesis stands rejected and the alternative hypothesis is approved i.e. there is a linear relationship between the dependent and independent variables.